PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN MARTABAK PIZZA ORINS CABANG PONDOK GEDE JAKARTA - Tika Kartika Asri; Mujito Mujito; Wawan Hari Subagyo; Kezia Yuniar Event Napitupulu (Institut Teknologi dan Bisnis Dewantara, 2023)
The purpose of this study was to determine the effect of marketing mix variables partially or simultaneously on purchasing decisions for Martabak Pizza Orins Pondok Gede Jakarta Branch. The results showed that: (1) The results of hypothesis testing partially proved that product quality and promotion variables had an effect on purchasing decisions with a calculated t value of product quality variable of 2.938 > t table of 1.984 with a significance value of 0.000 <0.05. Meanwhile, price and location variables have no effect on purchasing decisions with a calculated t value of the price variable of 0.154 <t table 1.984 with a significance value of 0.878 > 0.05 and a calculated t value of the location variable of 1.743 <t table 1.984 with a significance value of 0.085 > 0 ,05. (2) The results of the simultaneous hypothesis test prove that simultaneously the variables of product quality, price, promotion and location influence purchasing decisions with a calculated F value of 35.767 > F table 2.310, with a significance of 0.000 <0.05 (3) Test results for the coefficient of determination an adjusted R² value of 0.601 is obtained, this proves that in this study purchasing decisions are simultaneously influenced by product quality, price, promotion and location variables by 60.1%, while the remaining 39.9%.